Clinical characteristics and risk factors for tuberculosis during the COVID-19 pandemic: a longitudinal analysis in a trans-border Ukrainian region - E. Lesnic; L.D. Todoriko (Infusion & Chemotherapy)
OBJECTIVE. To assess the dynamics of the clinical peculiarities and risk factors for tuberculosis (TB) during the coronavirus disease (COVID-19) pandemic through a longitudinal analysis in a trans-border Ukrainian region.